Timing Review Iddah Men Based on Reasoning on a Contrario in Positive Law in Indonesia - Anugerahayu, Ayang Afira; Setiawan, Muhammad Rifaldi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study explores the legal provisions concerning the waiting period (iddah) for men using A Contrario reasoning within Indonesia’s positive law framework. Adopting a normative legal research approach, the study finds that Indonesian positive law, particularly Law Number 1 of 1974 on Marriage jo Law Number 16 of 2019 and Government Regulation Number 9 of 1975, explicitly regulates iddah only for women following divorce or the death of a spouse. In contrast, no legal requirement mandates men to undergo a waiting period before remarrying. Applying the Argumentum A Contrario method, which derives legal interpretation by considering the inverse of existing provisions, the study concludes that since the law exclusively prescribes iddah for women, men are not legally required to observe a waiting period.